The B.E. Journal of Theoretical Economics : (De Gruyter, 2001)
The B.E. Journal of Theoretical Economics (BEJTE) is a leading venue for top-notch economic theory, both pure and applied. Topics include contract theory, decision theory, game theory, general equilibrium theory, and mechanism design both pure and applied to such areas as industrial organization, public finance, labor and law and economics.